PENGEMBANGAN DESTINASI WISATA BUDAYA NAGARI KOTO HILALANG MELALUI WEBSIT NAGARI - Silvia Rosa; Miftahul Asraf; Dina Amalia; Septia Herman (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
This activity aims to help publicize the potential of the Koto Hilalang Nagari as one of the Cultural Tourism Village areas in Solok Regency, West Sumatra Province. The method of activity carried out is to make a design application for internet-based tourism promotion. This designed application can be inputted all the time by the Nagari community itself, especially by officers in the village office or the Nagari guardian's office. The results of the Andalas University Student Community Service program as agents of change in society during the 2019 Community Service Program in the village of Koto Hilalang are the availability of a website to promote and publicize the beauty of Nagari Koto Hilalang as a cultural tourism destination in the Solok Regency. The website can contain various kinds of Koto Hilalang's Nagari artistic potential to be promoted to a broader audience. This promotion is expected to invite more tourists to visit Nagari Koto Hilalang, Kubung District, Solok Regency.